Management of Visual Hallucinations in Schizophrenia Patients in Mental Rehabilitation Settings Auditory: A Nursing Case Study - Sugih Permana, Gin Gin; Ridwan Rifai, Mohamad; Riansyah, Alvi (CV. Literasi Publikasi Indonesia, 2025)
Schizophrenia is a chronic mental disorder that affects the way a person thinks, feels, and behaves. One of the most common positive symptoms is hallucinations, including visual hallucinations, which can significantly interfere with a patient's daily functioning. Proper management of visual hallucinations is essential to improving the patient's quality of life. This case study aims to examine the implementation of nursing care for patients with visual hallucinations due to schizophrenia and to evaluate the effectiveness of the interventions provided in reducing hallucination symptoms. This study uses a case study design with a qualitative approach. The research subject is a 28-year-old male patient who experiences visual hallucinations due to schizophrenia. Data collection was conducted through interviews, observations, and nursing documentation during the treatment period at the Garut mental rehabilitation clinic. The results of the assessment showed that the patient experienced visual hallucinations in the form of black shadows that followed his movements. The main nursing diagnosis that emerged was sensory perception disorder: visual hallucinations. The interventions provided included reality therapy, group activity therapy, health education, and pharmacotherapy. After 14 days of treatment, there was a decrease in the frequency of hallucinations from 8-10 times/day to 2-3 times/day. Comprehensive nursing care with a holistic approach proved to be effective in managing